Mutations in Drosophila tRNA processing factors cause phenotypes similar to Pontocerebellar Hypoplasia. - Schmidt, C.A.; Min, L.Y.; McVay, M.H.; Giusto, J.D.; Brown, J.C.; Salzler, H.R.; Matera, A.G. (Biology open, 2022)
Mature transfer (t)RNAs are generated by multiple RNA processing events, which can include the excision of intervening sequences. The tRNA splicing endonuclease (TSEN) complex is responsible for cleaving these intron-containing pre-tRNA transcripts. In humans, TSEN copurifies with CLP1, an RNA kinase. Despite extensive work on CLP1, its in vivo connection to tRNA splicing remains unclear. Interestingly, mutations in CLP1 or TSEN genes cause neurological diseases in humans that are collectively termed Pontocerebellar Hypoplasia (PCH). In mice, loss of Clp1 kinase activity results in premature death, microcephaly and progressive loss of motor function. To determine if similar phenotypes are observed in Drosophila, we characterized mutations in crowded-by-cid (cbc), the CLP1 ortholog, as well as in the fly ortholog of human TSEN54. Analyses of organismal viability, larval locomotion and brain size revealed that mutations in both cbc and Tsen54 phenocopy those in mammals in several details. In addition to an overall reduction in brain lobe size, we also found increased cell death in mutant larval brains. Ubiquitous or tissue-specific knockdown of cbc in neurons and muscles reduced viability and locomotor function. These findings indicate that we can successfully model PCH in a genetically-tractable invertebrate.